Modified ghee/clarified butter composition for food technology - Norazlianie, Sazali; Asogan, Arjun (2021)
Breeds of cows contribute to increase solid and fats in milk. Feed,veterinary knowledge and animal welfare were analyzed for ghee production. Different stages of prototype are built with different configurations and state. The best state of ghee are identified for commercialization. Product has been sold to market